2013
DOI: 10.1590/0103-6440201302223
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Smile Esthetics Varies Between Patients and Dental Professionals When Recession Defects are Present

Abstract: The aim of this study was to compare the smile esthetic perception of patients, dental students and dentists faced to different situations concerning gingival margin position. A total of 123 individuals (41 patients, 41 dental students and 41 dentists) completed a structured questionnaire and evaluated 6 pictures of the same smile modified in Adobe Photoshop® image-editing software representing: no gingival recession, 2 mm recession in one maxillary lateral incisor, 2 mm recession in both maxillary lateral inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
6
24
0
4
Order By: Relevance
“…Similarly, for color or shade of the crown at the margins, 59 of the total patients were satisfied with the results although only 26 of the cases were verified to be correct by the experts. These results are in accordance with the study by Musskopf et al 18 who concluded that patients and prosthodontists have different perceptions related to symmetry and esthetics around gingival margins of cemented crowns. 19 Moreover, patient's ability to detect symmetry cannot be relied when the evaluation is miniscule.…”
Section: Patient Dentist Evaluation Of the Quality Of Esthetic Of Cemsupporting
confidence: 93%
“…Similarly, for color or shade of the crown at the margins, 59 of the total patients were satisfied with the results although only 26 of the cases were verified to be correct by the experts. These results are in accordance with the study by Musskopf et al 18 who concluded that patients and prosthodontists have different perceptions related to symmetry and esthetics around gingival margins of cemented crowns. 19 Moreover, patient's ability to detect symmetry cannot be relied when the evaluation is miniscule.…”
Section: Patient Dentist Evaluation Of the Quality Of Esthetic Of Cemsupporting
confidence: 93%
“…GR may be an expression of destructive periodontal disease, and there is also evidence associating periodontitis with worst quality of life [4][5][6][7] . Recession defects have also been associated with esthetic complaints 8,25,26 , and this may be linked to lower quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors have observed that subjective perception can greatly influence the judgment of facial and smile features. Several clinical studies [6][7][8] as well as systematic reviews 9 have been performed to define the threshold values of acceptance for different smile characteristics from the point of view of laypeople. The majority of studies have been conducted involving adult observers, with few studies considering the perceptions of children and adolescents.…”
Section: Introductionmentioning
confidence: 99%